2007
DOI: 10.1029/2007gl030019
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectrical evidence of bicontinuum transport in groundwater

Abstract: [1] Bicontinuum models and rate-limited mass transfer (RLMT) explain complex transport behavior (e.g., long tailing and rebound) in heterogeneous geologic media, but experimental verification is problematic because geochemical samples represent the mobile component of the pore space. Here, we present geophysical evidence of RLMT at the field scale during an aquifer-storage and recovery experiment in a fractured limestone aquifer in Charleston, South Carolina. We observe a hysteretic relation between measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 23 publications
2
100
0
Order By: Relevance
“…However, characterization and sampling of less mobile pore space and associated reactive processes have been historically problematic [Jørgensen, 1977;Dentz et al, 2011]. These issues are primarily attributed to traditional fluid sampling of the saturated subsurface preferentially drawing water from mobile porosity [Harvey, 1993;Harvey and Gorelick, 2000;Singha et al, 2007]. If variability in carbon availability alone was responsible for redox zonation (e.g., microzones have similar hydraulic connectivity to bulk HZ sediments), we would expect stronger signals regarding embedded redox zones when collecting pore water samples.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, characterization and sampling of less mobile pore space and associated reactive processes have been historically problematic [Jørgensen, 1977;Dentz et al, 2011]. These issues are primarily attributed to traditional fluid sampling of the saturated subsurface preferentially drawing water from mobile porosity [Harvey, 1993;Harvey and Gorelick, 2000;Singha et al, 2007]. If variability in carbon availability alone was responsible for redox zonation (e.g., microzones have similar hydraulic connectivity to bulk HZ sediments), we would expect stronger signals regarding embedded redox zones when collecting pore water samples.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Fortunately, emerging microscale and field-scale techniques have potential to better characterize less mobile porosity. For example, measurement of fluid conductivity (σ f ) and co-located bulk conductivity (σ b ) during ionic tracer tests provide information on mobile-immobile exchange [Singha et al, 2007;Briggs et al, 2013b]. Relatively tight pores that connect through pockets of fine-grained or organic material are expected to contribute to the bulk conductivity signal; therefore, electrical data can be collected in situ to directly describe less mobile exchange characteristics.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Results from an electrical geophysical dataset obtained during an aquifer-storage and recovery (ASR) test in Charleston, South Carolina indicate that direct-current resistivity methods may be able to help estimate mass transfer behavior in situ (Singha et al, 2007). The authors observed hysteresis between fluid electrical conductivity (EC) and the bulk apparent EC, which contradicts common rock physics relations, and suggested that the hysteresis is an effect of dual-domain mass transfer.…”
Section: Introductionmentioning
confidence: 88%
“…To evaluate the electrical response to tracer behavior, we simulate a push-pull type test, loosely mimicking the data collection procedure described in Singha et al (2007). The injection/extraction well was represented by a series of 32 points spaced 1 m apart vertically from 9 m to 40 m below the simulated land surface and 46.5 m to the ) 0.075 Dispersivity, primary direction (immobile, α 1 ) 0 m Dispersivity, secondary direction (immobile,α 2 ) 0 m right of the model origin, near the midpoint of the system.…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation